Analisis Semiotika Bias Gender dalam Film Ngeri-Ngeri Sedap (Karya Bene Dion Raja Gukguk) - Bangun, Dinda Almunawaroh; Azhar, Anang Anas (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Current Gender issues have not shown equality. Inequality between women and men almost occurs in all fields such as education, politics and even family. Film is a representation of the form of human daily life, both based on true stories and science fiction from writers or directors. This study uses descriptive qualitative methodology by identifying and interpreting myths, denotations, and indicators of Gender inequality in films.. Researchers found three scenes in the film